Sexual Crimes, Abortion, and Chemical Castration Punishment in Indonesia: A Legal and Ethical Review - Wijoyo, Suryo; Herman, KMS (Indonesian Journal of Multidisciplinary Science, 2025)
Sexual crimes are a serious and growing problem in Indonesia and have far-reaching implications, including abortion. Indonesia's abortion regulations have evolved, particularly in providing exceptions for victims of sexual crimes with certain gestational age limits. However, the implementation of this policy still faces challenges, such as complex administrative procedures, limited health care facilities, and social stigma. On the other hand, the government has implemented chemical castration as an effort to reduce the number of sexual crimes against children. This policy aims to reduce the sexual drive of offenders and prevent recidivism. However, its effectiveness is still debated, especially regarding medical aspects, ethics, and limited medical personnel in its implementation. This research uses a normative juridical approach with a literature study mOethod to analyze the applicable regulations as well as the challenges of implementing policies related to sexual crimes, abortion, and chemical castration in Indonesia. The results show that the existing regulations still have some weaknesses in implementation, especially in access to health services for victims of sexual violence and the effectiveness of chemical castration in reducing the number of sexual crimes. Therefore, a more comprehensive approach is needed, including improved abortion regulations, improved services for victims, and sexual education as a long- term prevention effort against sexual crimes.